IS THE DORSAL PERCUTANEOUS APPROACH WELL-FOUNDED FOR OSTEOSYNTHESIS OF SCAPHOID FRACTURES? - Drac, Pavel; Cizmar, Igor; Hrbek, Jan (Biomedical papers, 2009)
Aims: To compare complications associated with dorsal percutaneous and limited dorsal approaches in the surgical treatment of fractured scaphoid bone.Methods: A total of 51 patients with acute type A2, B2 and B3 scaphoid fractures were treated by limited dorsal approach. During follow-up examinations we analysed the functional outcome and per- and post-operative complications, and we compared them with studies using the dorsal percutaneous approach.Results: We found fewer complications using the limited dorsal approach.Conclusions: We found no advantages of the dorsal percutaneous approach. In addition to a favourable functional outcome, the limited dorsal approach permits visualization of the screw insertion point and of the fracture line course, and prevents insufficient screw sinking underneath the bone cartilage and malunion.
Keywords: Scaphoid fractures/Limited dorsal approach/Dorsal percutaneous approach/Complications